2022
DOI: 10.1007/s10725-022-00838-5
|View full text |Cite
|
Sign up to set email alerts
|

A simple, rapid, and quantifiable system for studying adventitious root formation in grapevine

Abstract: Woody cutting is customarily utilized as material in research of grape adventitious root formation (ARF).However, phenotypic heterogeneity caused by the complex background in uenced its use for molecular mechanism research of ARF of grape. The present study tested various types of explants from grape tissue culture plantlets and found the whole leaf: blade with petiole (LP) was the simplest unit that can easily form adventitious root (AR). LP explants which can be easily obtained, directly generate ARs via de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…The onset of AR was always delayed by NPA, regardless of the type of treatment. A similar response has been observed in other species such as pine, oak and grapevine [ 32 , 47 , 48 ]. In addition, auxin-induced activation of target-competent cells was not greatly impaired by the temporal (5 day) post-application of NPA, as once NPA was removed from the medium the cells were able to resume division and proceed to the rooting pathway.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The onset of AR was always delayed by NPA, regardless of the type of treatment. A similar response has been observed in other species such as pine, oak and grapevine [ 32 , 47 , 48 ]. In addition, auxin-induced activation of target-competent cells was not greatly impaired by the temporal (5 day) post-application of NPA, as once NPA was removed from the medium the cells were able to resume division and proceed to the rooting pathway.…”
Section: Discussionsupporting
confidence: 84%
“…The function of auxin signaling and transport in adventitious root formation have been reported in different species [ 2 , 52 , 53 , 54 ]. Inhibitors of plant auxin transport, such as NPA, were shown to delay and inhibit adventitious root formation [ 32 , 48 , 49 , 55 , 56 , 57 ]. A direct correlation between inhibition of AR by NPA and suppression of the 24 h peak of IAA during induction of adventitious roots was also demonstrated in petunia [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results in Table 2 show that the NAA soaked concentration at various concentrations (S0, S1, S2 and S3) had no significant effect on the time of emergence of leaf on grape cuttings seedlings. The leaf emergence is influenced by the interaction between auxins and cytokinins found in cuttings (Salem et al, 2022); (Chang et al, 2022). In this study, as shown in Figure 2 it was suspected that the new root system was formed in the 2nd week so endogenous auxin had not been produced because the absorption of NAA soaked concentration was used by cuttings for initiation of root formation.…”
Section: Leaf Emergence Timementioning
confidence: 76%
“…In this study, the rejuvenated and mature cuttings both displayed a decrease in tZR levels, but this decrease was more pronounced at 14 days in the rejuvenated shoots, which was in agreement with the general observation that cytokinin depletion participates in the induction of adventitious roots in cuttings [ 38 ]. GAs have been shown to significantly inhibit ARF and development [ 40 ]. External application of GAs has been shown to inhibit rooting, possibly by inhibiting auxin polar transport [ 41 ].…”
Section: Discussionmentioning
confidence: 99%